1994
DOI: 10.1128/aac.38.2.288
|View full text |Cite
|
Sign up to set email alerts
|

Bisheteroarylpiperazine reverse transcriptase inhibitor in combination with 3'-azido-3'-deoxythymidine or 2',3'-dideoxycytidine synergistically inhibits human immunodeficiency virus type 1 replication in vitro

Abstract: Bisheteroarylpiperazine compounds are nonnucleoside reverse transcriptase inhibitors of human immunodeficiency virus type 1 (HIV-1). To provide a rationale for combination therapy with a second-generation bisheteroarylpiperazine, we investigated the effect of U-90152 in combination with 3'-azido-3'-deoxythymidine (AZT) or 2',3'-dideoxycytidine (ddC). HIV-1-infected cells were cultured in the presence of test compounds, and drug effects on p24 core antigen production were measured by an enzyme-linked immunosorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 31 publications
1
32
0
1
Order By: Relevance
“…Despite many studies devoted to this topic, the molecular mechanism underlying the antiviral synergy of combinations of reverse transcriptase inhibitors is in most cases unknown. The synergistic inhibition of HIV replication in cell culture has been reported for many combinations of nucleosidic and NNRTI inhibitors including, among others, bis(heteroaryl)piperazine derivates (29), pyridinone derivates (30), nevirapine (13), HEPT derivates (14), TIBO derivates (15,31), or canalolide A (16). However, other studies have shown that the same combinations showed no synergy in inhibiting RT activity in vitro (17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Despite many studies devoted to this topic, the molecular mechanism underlying the antiviral synergy of combinations of reverse transcriptase inhibitors is in most cases unknown. The synergistic inhibition of HIV replication in cell culture has been reported for many combinations of nucleosidic and NNRTI inhibitors including, among others, bis(heteroaryl)piperazine derivates (29), pyridinone derivates (30), nevirapine (13), HEPT derivates (14), TIBO derivates (15,31), or canalolide A (16). However, other studies have shown that the same combinations showed no synergy in inhibiting RT activity in vitro (17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…A synergistic antiviral effect in vitro has also been reported for two-drug combinations involving ZDV and several other NNRTls including DLV, pyridinone L-697,639 and nevirapine (Chong et al, 1994;Richman et al, 1991;Goldman et al, 1991). Separately, Balzarini et al (1996) reported that when combined with 3TC, several NNRTls, including DLV, more readily suppress viral 'breakthrough', and may delay the emergence of resistant virus.…”
Section: Discussionmentioning
confidence: 96%
“…This is equivalent to 70% of the peak viral titre achievable on day 7 post-infection. PBMC antiviral assays were set up as described previously (Chong et a!., 1994). The percentage inhibition of HIV replication on day 5 of treatment was determined by comparing HIV p24 antigen levels in the supernatant of infected cells treated with inhibitor versus supernatant from the control cultures without compound.…”
Section: Antiviral Assaymentioning
confidence: 99%
See 2 more Smart Citations